2003
DOI: 10.1590/s0100-879x2003001100016
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and N-acetyl-serotonin cross the red blood cell membrane and evoke calcium mobilization in malarial parasites

Abstract: The duration of the intraerythrocytic cycle of Plasmodium is a key factor in the pathogenicity of this parasite. The simultaneous attack of the host red blood cells by the parasites depends on the synchronicity of their development. Unraveling the signals at the basis of this synchronicity represents a challenging biological question and may be very important to develop alternative strategies for therapeutic approaches. Recently, we reported that the synchrony of Plasmodium is modulated by melatonin, a host ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 19 publications
2
38
0
4
Order By: Relevance
“…Thus higher concentrations may be necessary to elicit maximal amplitude and immediate responses at the level of inositol phosphate generation and Ca 2ϩ mobilization. Previous studies from our laboratory have shown that the effects of melatonin on parasite Ca 2ϩ release and synchronized progression through the cell cycle are blocked by the PLC inhibitor U73122 (13,14,40). Importantly, the activation of PLC by melatonin in P. falciparum is corroborated in this study without the use of pharmacological inhibitors and the potential nonspecific effects of these compounds.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Thus higher concentrations may be necessary to elicit maximal amplitude and immediate responses at the level of inositol phosphate generation and Ca 2ϩ mobilization. Previous studies from our laboratory have shown that the effects of melatonin on parasite Ca 2ϩ release and synchronized progression through the cell cycle are blocked by the PLC inhibitor U73122 (13,14,40). Importantly, the activation of PLC by melatonin in P. falciparum is corroborated in this study without the use of pharmacological inhibitors and the potential nonspecific effects of these compounds.…”
Section: Discussionsupporting
confidence: 68%
“…As mentioned in the "Results," increases in inositol polyphosphates by melatonin concentrations below 100 M were not significant. Melatonin in the lower range is capable of exerting effects on life cycle progression when included in RBC malaria parasite cultures (13,40). However, these cell cycle progression effects of melatonin occur on a much slower timescale than the 20-min incubations in the present experiments, and the associated Ca 2ϩ increases are also slower and of lower amplitude (40).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…1 and 4C) suggest that the activation of PfPKB by CaM is dependent on calcium, it was important to investigate the mechanism via which parasitic calcium regulates PfPKB. Intracellular calcium levels of the parasite are tightly regulated in Plasmodium, and inhibitors of phospholipase C (PLC) (21), which block inositol 1,4,5-trisphosphate formation, prevent release of free calcium from intracellular parasite stores (22,23). To investigate the role of PLC in PfPKB activation, schizonts were incubated with either U73122, a specific inhibitor of PLC, or its less potent analogue U73322.…”
Section: Resultsmentioning
confidence: 99%
“…PLC inhibitor U73122 has been successively used in Plasmodium to block calcium release (22). Using this inhibitor we were able to demonstrate that PLC is the upstream regulator of PfPKB as it mediates calcium release crucial for PfPKB activation.…”
Section: Discussionmentioning
confidence: 99%